Mesoscale Transcranial Spontaneous Activity Mapping in GCaMP3 Transgenic Mice Reveals Extensive Reciprocal Connections between Areas of Somatomotor Cortex - Vanni, Matthieu P. (J Neurosci, 2014)
Transgenic mice expressing genetically encoded activity indicators are an attractive means of mapping mesoscopic regional functional cortical connectivity given widespread stable and cell-specific expression compatible with chronic recordings. Cortical functional connectivity was evaluated using wide-field imaging in lightly anesthetized Emx1-creXRosa26-GCaMP3 mice expressing calcium sensor in cortical neurons. Challenges exist because green fluorescence signals overlap with endogenous activity-dependent autofluorescence and are affected by changes in blood volume and oxygenation. Under the conditions used for imaging and analysis (0.1–1 Hz frequency band), autofluorescence and hemodynamic effects contributed 3% and 8% of the SD of spontaneous activity-dependent GCaMP3 fluorescence when signals were recorded through intact bone. To evaluate the accuracy and sensitivity of this approach, the topology of functional connections between somatomotor cortex (primary S1 and secondary S2 somatosensory, and primary motor cortex M1) was estimated. During sequences of spontaneous activity, calcium signals recorded at each location of area S1 were correlated with activity in contralateral area S1, ipsilateral area S2, and bilateral areas M1. Reciprocal results were observed when “seed pixels” were placed in S2 and M1. Coactivation of areas implies functional connections but could also be attributed to both regions receiving common upstream drive. These apparent connections revealed during spontaneous activity coactivation by GCaMP3 were confirmed by intracortical microstimulation but were more difficult to detect using intrinsic signals from reflected red light. We anticipate GCAMP wide-field imaging will enable longitudinal studies during plasticity paradigms or after models of CNS disease, such as stroke, where the weighting within these connectivity maps may be altered.